KNOWLEGDE OF POST-OF-MOTHERS AND INCIDENCE OF BREAST ENGORGEMENT: STUDY CROSS SECTIONAL - Nency Agustia; Avriana Faiza Shalma (LPPM STIKES Al-Ma'arif Baturaja, 2026)
The achievement of exclusive breastfeeding in OKU Regency is still low, namely 49.3%, this figure shows a gap of 30.7% from the national target that has been set, namely 80%.This is influenced by the knowledge of mothers during the postpartum period. Mothers who experience breast milk engorgement will stop breastfeeding because it feels painful. The purpose of this study was to determine the relationship between the level of knowledge of postpartum mothers and the incidence of breast milk engorgement in the working area of ​​Tanjung Agung Health Center, Ogan Komering Ulu Regency. This type of research is descriptive using a cross-sectional approach. The study population was postpartum mothers in the working area of ​​Tanjung Agung Health Center with a sample size of 65 respondents. Sampling was carried out by multistage sampling where the independent variable in this study was the knowledge of postpartum mothers, the dependent variable was the incidence of breast milk engorgement. Data analysis used the chi-square test. The results of the study were that there was a relationship between the level of knowledge of postpartum mothers and the incidence of breast milk engorgement with a p value of 0.000. The knowledge of postpartum mothers was lacking as much as 94.1% for the prevalence of breast milk engorgement as much as 76.9% in the working area of ​​Tanjung Agung Health Center.